MODEL OF TEACHING PROFESSION SPECIFIC BILATERAL TRANSLATION - Yana Fabrychna (Naukovì Zapiski Ternopìlʹsʹkogo Nacìonalʹnogo Pedagogìčnogo Unìversitetu Imenì Volodimira Gnatûka. Serìâ: Pedagogìka, 2017)
The article deals with the author’s interpretation of the process of teaching profession specific bilateral translation to student teacher of English in the Master’s program. The goal of the model of teaching profession specific bilateral translation development is to determine the logical sequence of educational activities of the teacher as the organizer of the educational process and students as its members. English and Ukrainian texts on methods of foreign languages and cultures teaching are defined as the object of study. Learning activities aimed at the development of student teachers of English profession specific competence in bilateral translation and Translation Proficiency Language Portfolio for Student Teachers of English are suggested as teaching tools. The realization of the model of teaching profession specific bilateral translation to student teachers of English in the Master’s program is suggested within the module topics of the academic discipline «Practice of English as the first foreign language»: Globalization; Localization; Education; Work; The role of new communication technologies in personal and professional development. We believe that the amount of time needed for efficient functioning of the model is 48 academic hours, which was determined by calculating the total number of academic hours allotted for the academic discipline «Practice of English as the first foreign language» in Ukrainian universities. Peculiarities of the model realization as well as learning goals and content of class activities and home self-study work of students are outlined.